B-type natriuretic peptide in patients with asymptomatic severe aortic stenosis. Issue 5 (7th December 2018) - Nakatsuma, Kenji; Taniguchi, Tomohiko; Morimoto, Takeshi; Shiomi, Hiroki; Ando, Kenji; Kanamori, Norio; Murata, Koichiro; Kitai, Takeshi; Kawase, Yuichi; Izumi, Chisato; Miyake, Makoto; Mitsuoka, Hirokazu; et al.
Abstract : Objectives: We sought to evaluate the prognostic impact of the B-type natriuretic peptide (BNP) levels in patients with asymptomatic severe aortic stenosis (AS), who were not referred for aortic valve replacement (AVR). Methods: We used data from a Japanese multicentre registry, the Contemporary outcomes after sURgery and medical tREatmeNT in patients with severe Aortic Stenosis Registry, which enrolled 3815 consecutive patients with severe AS. Of those, 387 asymptomatic patients who were not referred for AVR without left ventricular dysfunction and very severe AS were subdivided into four groups based on their BNP levels (BNP<100 pg/mL, n=201; 100≤BNP<200 pg/mL, n=94; 200≤BNP<300 pg/mL, n=42 and BNP>300 pg/mL, n=50). Results: The cumulative 5-year incidence of AS-related events (aortic valve-related death or heart failure hospitalisation) was incrementally higher with increasing BNP level (14.2%, 29.6%, 46.3% and 47.0%, p<0.001). After adjusting for confounders, the risk for AS-related events was incrementally greater with increasing BNP levels (HR: 1.97, 95% CI: 0.97 to 3.98, p=0.06; HR: 3.59, 95% CI: 1.55 to 8.32, p=0.03 and HR: 7.38, 95% CI: 3.21 to 16.9, p<0.001, respectively). Notably, asymptomatic patients with BNPlevels of <100 pg/mL had an event rate of only 2.1% at 1 year. Conclusions: Increased BNP level was associated with a higher risk for AS-related adverse events in patients with asymptomatic severe AS with normal left ventricular ejection fraction who were not referred for AVR. Asymptomatic patients with BNP levels of <100 pg/mL had relatively low event rate, who might be safely followed with watchful waiting strategy. Trail registration number: UMIN000012140.